2017
DOI: 10.1158/1055-9965.epi-17-0346
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antihypertensive Medications and Risk of Adverse Breast Cancer Outcomes in a SEER–Medicare Population

Abstract: Background It is unclear if use of common antihypertensive medications influences the risk of adverse breast cancer outcomes. Methods Using the linked Surveillance, Epidemiology and End-Results (SEER)-Medicare database, we identified 14,766 women between ages 66 and 80 years diagnosed with incident stage I/II breast cancer between 2007–2011. Medicare Part D data were obtained to characterize women’s post-cancer use of various antihypertensive medications. Outcomes included a second breast cancer event (SBCE,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 37 publications
2
35
1
Order By: Relevance
“…It was reported that there had no evidence that CCB use was associated with a better or worse survival in cancer patients in Asian and Caucasian populations. 47 On the contrary, association of CCB use with risks of breast cancer outcomes has also been reported, 48 and CCBs have been associated with increased cancer recurrence in patients with head and neck squamous cell carcinoma. 49 CCBs also have been associated with decreased survival in certain cancers when compared with β-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there had no evidence that CCB use was associated with a better or worse survival in cancer patients in Asian and Caucasian populations. 47 On the contrary, association of CCB use with risks of breast cancer outcomes has also been reported, 48 and CCBs have been associated with increased cancer recurrence in patients with head and neck squamous cell carcinoma. 49 CCBs also have been associated with decreased survival in certain cancers when compared with β-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the sample was insufficient to allow subgroup analysis of BB effects by specific CVD types (e.g., arrhythmia, coronary artery disease). Furthermore, a lack of BB dose data inhibited exploratory analysis of the dose-response relationship was not possible (29,30). While BB use was independently and significantly associated with worsened OS in the total and sensitivity cohort, the associations with PFS was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This is, to date, the first observational study assessing the influence of furosemide use on esophageal/gastric cancer mortality. A limited number of studies have investigated furosemide use and cancer risk or survival, concentrated on investigations into breast, skin and lip cancer but not esophageal/gastric cancer, and furosemide was not the primary exposure of interest [2628]. No consistent associations were observed for furosemide use and risk or survival of these cancers from human studies.…”
Section: Discussionmentioning
confidence: 99%